A CULTURAL APPROACH TO DEVELOPING PUBLIC RELATIONS IN SCHOOLS TO ALIGN LOCAL VALUES - Hani, Ummi; Rifai, Moh; Iman, Dian Zulfatul (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2024)
Public relations (PR) in schools is increasingly essential in facing the challenges of globalization, especially in aligning local values with modern communication practices. This research explores applying a cultural approach in PR strategies at MA Sunan Muria Pategalan, Jatibanteng District, Situbondo Regency, which has a rich local culture. Using qualitative methods with case studies, data was collected through observation, in-depth interviews with key informants (school principal, head of public relations, student parents), and documentation related to school homework activities. Data were analyzed using an analysis model that included condensation, presentation, and conclusion. The research results show that integrating local culture in PR can strengthen relations between schools and communities, create more relevant and meaningful communication, and increase community acceptance of schools. This research emphasizes the importance of understanding and respecting local cultural values in building harmonious relationships.